1994
DOI: 10.1111/j.1365-2125.1994.tb04308.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of sex‐steroid hormones on the regulation of lymphocyte beta 2‐adrenoceptors during the menstrual cycle.

Abstract: 1 Up to 40% of female asthmatic subjects suffer a premenstrual deterioration in their condition which may be ameliorated by progesterone supplementation, although the mechanism responsible for this phenomenon is not understood.In vitro studies have shown that female sex-steroid hormones potentiate the bronchorelaxant effect of isoprenaline, whilst in vivo it has been shown that females exhibit greater sensitivity of systemic 02-adrenoceptor responses. 2 The aim of the present study was to determine whether cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
1
4

Year Published

1997
1997
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(47 citation statements)
references
References 19 publications
1
41
1
4
Order By: Relevance
“…Indeed, some studies reported that the luteal phase is characterized by higher expression of β 2 -adrenoceptors on lymphocytes, and by a higher lymphocyte cAMP response to isoproterenol (Wheeldon et al, 1994). While NK cells comprise only about 15% of the lymphocyte population, they were reported to express the highest levels of β 2 -adrenoceptors (Landmann, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, some studies reported that the luteal phase is characterized by higher expression of β 2 -adrenoceptors on lymphocytes, and by a higher lymphocyte cAMP response to isoproterenol (Wheeldon et al, 1994). While NK cells comprise only about 15% of the lymphocyte population, they were reported to express the highest levels of β 2 -adrenoceptors (Landmann, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports in this area have not been consistent in terms of gender difference. Wheeldon et al (1994) reported that females showed higher lymphocyte ␤ 2 -adrenoceptor density (B max ) and stimulated cAMP levels only during luteal phase than male subjects. Halper et al (1984) reported that betareceptor binding indices (B max ) in general did not differ between males and females; whereas, in older subjects, females showed higher cAMP ratio levels than males.…”
Section: Discussionmentioning
confidence: 99%
“…Since β 2 -adrenergic mechanisms have been reported to be sexually dimorphic (Barker et al, 2005;de Coupade et al, 2004;Hinojosa-Laborde et al, 1999;Krieg et al, 1986;Mills et al, 1996;Tan et al, 1997;Wheeldon et al, 1994), the present study investigated the ability of β 2 -adrenergic receptors to modulate neutrophil recruitment, using wild-type (FVB) and β 2 -adrenergic receptor knockout mice (bred on a congenic FVB background). Of note, in a comparison of inflammation in the lungs of 9 mouse strains, after ovalbumin sensitization and aerosol challenge the FVB strain had fewer infiltrating leukocytes than 4 other strains, but similar to BALB/C, C57/BL and C3H/HeJ strains (Whitehead et al, 2003).…”
Section: Introductionmentioning
confidence: 99%